Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Average = sum/no of observations

Total A. = sum/6

x = sum/6

6x = sum

Avg. of 1st 3 = sum of 1 st three/ 3

y = sum of 1st three/3

3y = sum of 1st three

Avg. of last 3 = sum of last three / 3

z = sum of last three/3

3z = sum of last three

Sum of 1st three + Sum of last three = Total Sum

3y + 3z = 6x

y + z = 2x

x = y + z / 2

Total A. = sum/6

x = sum/6

6x = sum

Avg. of 1st 3 = sum of 1 st three/ 3

y = sum of 1st three/3

3y = sum of 1st three

Avg. of last 3 = sum of last three / 3

z = sum of last three/3

3z = sum of last three

Sum of 1st three + Sum of last three = Total Sum

3y + 3z = 6x

**3(y + z) = 3*2x**

y + z = 2x

x = y + z / 2